2019
DOI: 10.3390/bs9090096
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Barriers to Digital Living in Older Adults: Computer Anxiety as Predictive Mechanism for Technophobia

Abstract: This study aimed to investigate the emotional impact of technology use in an Italian adult population and to detect technophobia. This cross-sectional study was conducted with 117 Italian participants (age range of 50–67 years). Measured variables were computer anxiety and technology use ability. The results revealed technophobia features in the Italian adult population related to inadequate management of technology. One-way analysis of variance and Bonferroni’s post-hoc analysis showed that non-autonomous (p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 25 publications
4
53
0
Order By: Relevance
“…Particularly, we wanted to investigate the adulthood application in the daily digital solutions in order to highlight the weakness and strengthens. Following our preview study (Di Giacomo et al, 2019), findings confirmed the rule of self-perception in digital application in order to exploit digital living benefits. Our study evidenced as the low digital skills in adulthood isn't associated to gender, aging or education variables; the computer anxiety in adulthood is related to the self-perception of own ability to use the technology autonomously.…”
Section: Discussionsupporting
confidence: 74%
“…Particularly, we wanted to investigate the adulthood application in the daily digital solutions in order to highlight the weakness and strengthens. Following our preview study (Di Giacomo et al, 2019), findings confirmed the rule of self-perception in digital application in order to exploit digital living benefits. Our study evidenced as the low digital skills in adulthood isn't associated to gender, aging or education variables; the computer anxiety in adulthood is related to the self-perception of own ability to use the technology autonomously.…”
Section: Discussionsupporting
confidence: 74%
“…Skills and access were not adjusted for in these studies, however, and our results suggest that they are of importance. For example, in Italy researchers found that a substantial proportion of those aged 50 years or older were not digitally skilled [ 28 ]. Because skills seem to be crucial for older people to benefit from online services, training should be provided for them [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the results defied the common perception that older individuals are apprehensive about technology [ 15 ]. Previous research in this area has shown that the ageing population feared technology and were less likely to use them [ 15 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the results defied the common perception that older individuals are apprehensive about technology [ 15 ]. Previous research in this area has shown that the ageing population feared technology and were less likely to use them [ 15 , 28 ]. Generally, the acceptance of new digital solutions and innovative technology by patients and carers relies on their anxieties and feelings of insecurity concerning the device/technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation